2018
DOI: 10.3892/etm.2018.5710
|View full text |Cite|
|
Sign up to set email alerts
|

Anticancer activity of 23,24-dihydrocucurbitacin B against the HeLa human cervical cell line is due to apoptosis and G2/M cell cycle arrest

Abstract: Abstract. Cervical cancer is one of the primary causes of cancer-associated mortality worldwide. Due to the increasing incidence of cervical cancer, multiple treatment options are required. Initial responses to chemotherapy and surgical interventions are generally positive, however patients often experience relapse and tumor recurrence. Currently, the effects of cucurbitacins on different types of cancer are being investigated, as they exhibit a wide variety of bioactivities. The anticancer activity of the cuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Ovarian cancer accounts for 0.152 million deaths annually and around 0.3 million new ovarian cases are diagnosed annually worldwide [13][14][15]. The clinical outcome is unsatisfactory due its diagnosis at advanced stages and unavailability of therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer accounts for 0.152 million deaths annually and around 0.3 million new ovarian cases are diagnosed annually worldwide [13][14][15]. The clinical outcome is unsatisfactory due its diagnosis at advanced stages and unavailability of therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphoinositide 3 kinase/protein kinase B/mechanistic target of rapamycin (PI3K/AKT/mTOR) cascade may play an important role in cancer tumorigenesis and progression and resistance to chemotherapy. The results indicated that DHCB decreased the expression of important proteins in the PI3K/Akt/mTOR cascade [16].…”
Section: Cucurbitacin B (1′)mentioning
confidence: 94%
“…HeLa is named so after Henrietta Lacks, a lady who died of cervical cancer in 1951 (13). Ever since the distribution of her cells, this cell line has been commonly used to evaluate the effects of various anticancer drugs (14). HeLa cells have been used to investigate the phytocomponents (plant-based components) and the apoptotic mechanism of the anti-cancer activity of the ethanolic extract of mango peel (15).…”
mentioning
confidence: 99%